Managing the Development of the Innovation Market in the Service Sector in the Republic of Kazakhstan - K. A. Kirdasinova; N. B. Omarbekova (Экономика: стратегия и практика, 2022)
An ability to innovate is more commonly observed as a crucial element in obtaining a sustainable competitive advantage. Although the issue of innovational development within product companies has been an object of research, there are still questions to answer regarding how innovational management should be conducted in service organizations, especially in the context of the Republic of Kazakhstan. The main aim of this investigation is to develop the new theoretical concept of stimulation of innovative processes among service providers in the Republic of Kazakhstan. Thus, the central question in this paper asks what measures should be taken to increase the competitiveness of domestic companies offering services by virtue of managing the market of innovations taking into account the national peculiarities. The results of this study provide an important opportunity to advance the understanding of the innovation market as the unique sphere from other industries can benefit from. As the result of the investigation, the authors proposed the theoretical concept including the element of a customer, whose role of co-producer is especially important in the service sphere. Also, because of the difference in the innovational activity and economic differences among the territorial division of the country, it is more effective to grant the local innovational offices more power to set the priority directions in service innovation for each region. The current research sets a new ground for the following investigations in the area of innovation management in the service industry in Kazakhstan.